PROYEKSI STOKASTIK PRODUKSI JAGUNG DI INDONESIA - Susi Puspita Sari; Agus Hudoyo; Achdiansyah Soelaiman (Lampung University, 2018)
Corn is a strategic commodity in the Indonesian economy because corn is for either food or feed. As an important agricultural commodity, the corn production is highly targeted by the Indonesian government, i.e. 24.70 million tons in 2019 or 125% of the 2015 corn production. This target is better stochastically forecasted that its result is an interval in a certain probability level. Therefore, the goal of this research is to stochastically forecast the corn production. The data are time series and obtained from the FAO and the Indonesian Central Bureau Statistics. The data is analyzed by econometrics. The result showed that the corn production would be 18.93 million tons in 2019 with its 95% confidence interval between 17.09 million tons and 20.76 million tons.Key words: corn, forecast, production, stochastic